2020
DOI: 10.1039/c9na00532c
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale lipid vesicles functionalized with a nitro-aniline derivative for photoinduced nitric oxide (NO) delivery

Abstract: Photo-controllable, non-toxic and bio-compatible nano-scale vesicles for the controllable release of nitric oxide (NO) have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…1235 Hexadecylamine-substituted 4-nitro-3-(trifluoromethyl)aniline 311 (Figure 48) was used by Jose and co-workers to prepare nanoscale lipid vesicles for photoinduced NO delivery (λ irr = 410 nm). 1236 However, even push-pull-substituted nitroarenes are poor chromophores (ε max ≈ 1000 M −1 cm −1 ) and must be sensitized to enable visible-light activation. Sortino and co-workers introduced the anthracene-based photoNORM 312, which releases NO upon irradiation with 420 nm light.…”
Section: Release Of Nitric Oxidementioning
confidence: 99%
“…1235 Hexadecylamine-substituted 4-nitro-3-(trifluoromethyl)aniline 311 (Figure 48) was used by Jose and co-workers to prepare nanoscale lipid vesicles for photoinduced NO delivery (λ irr = 410 nm). 1236 However, even push-pull-substituted nitroarenes are poor chromophores (ε max ≈ 1000 M −1 cm −1 ) and must be sensitized to enable visible-light activation. Sortino and co-workers introduced the anthracene-based photoNORM 312, which releases NO upon irradiation with 420 nm light.…”
Section: Release Of Nitric Oxidementioning
confidence: 99%
“…This significantly slower release from the vesicles could be attributed to the slow photodegradation of L.Ru-NO in the lipid bilayer as compared to the photodegradation in pure organic medium. 25 However, NO release kinetics studies indicate that among saturated lipids, L.Ru-NO@Lip2 having a shorter-alkyl-chain (C 14 ) DMPC shows a relatively slow release with a low rate constant (k = 0.083 min −1 ) and long half-lives (t 1/2 = 8.3 min) than the vesicles prepared by longer-alkyl-chain (C 16 and C 18 ) lipids DPPC and DSPC. The possible reason is that the shorter alkyl chains make the lipid bilayer membrane more fluid as compared to lipids with longer alkyl chains where bilayer membranes are tightly packed (Table 1 and Figure 4).…”
Section: Under Reflux Condition (Schemes 1 and S1)mentioning
confidence: 97%
“…21 However, photo-responsive NO-releasing molecules (photoNORMs) are of great importance as delivery of NO could be achieved by light, which is easily controllable, facilely available, non-invasive, sustainable, and renewable. 22 Over the past decade, several photo-responsive NO donor-based nanoplatforms have been reported, 23 such as upconversion nanoparticles, 24 nanovesicles, 25 micelles, 26 quantum dots, 27 graphene-based quantum dots 28 and nanosheets. 29 Ruthenium nitrosyl (Ru-NO) complexes have many advantages due to their low cytotoxicity, release of NO upon light exposure, and good chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The Bzimpy-LC embedded nanoscale probe Lipo-1 (4 mM) was prepared by following the earlier method reported by our research group. 25,27 Briey, Bzimpy-LC (1 mg) and lipid 1,2dioelyl-sn-glycero-3-phosphocholine (DOPC) (3.93 mg) were dissolved in chloroform (1000 mL). The solvent was evaporated under vacuum to get a lipid thin lm.…”
Section: Preparation Of Liposomes Lipo-1mentioning
confidence: 99%
“…Recently, many studies have shown the use of Cu 2+ complexes as a probe for the optical detection of anions such as cyanide (CN À ) and biological phosphates such as PPi and ATP in semiaqueous and aqueous solutions. 19,20,[24][25][26][27][28][29][30][31][32][33][34][35]36 Most of the small organic molecule-based cyanide probes have the disadvantage of water solubility; therefore, the use of organic solvent as a cosolvent is unavoidable. [37][38][39] The probe Lipo-1 works in a pure aqueous solution to detect copper with a good change in the emission signal.…”
Section: Binding Studies Of Lipo-1cu With Anionsmentioning
confidence: 99%